《美国佬》中的非洲流散与 "世界性主体". - 何卫华 (Foreign Literature Studies, 2025)
Chimamanda Ngozi Adichie is one of the most influential African diasporic writers of the 21st century. Through the diaspora and "homecoming" experiences of the protagonists, Ifemelu and Obinze, Adichie showcases a more genuine, nuanced, and more contemporary Nigeria in Americanah. Since the late 20th century, a significant number of Nigerians have begun to emigrate overseas, transforming the passive diaspora of the colonial era into an active one. In Adichie's writings, African women are portrayed as independent and self-determined, no longer the silent "other," with Ifemelu serving as a representative of such women. For Ifemelu, the experience of diaspora is a form of empowerment that provides her with a broader perspective, transforming her into a genuine "cosmopolitan subject." With the transcendent perspective of this "cosmopolitan subject," Adichie not only demystifies the West but also critically examines the internal issues of Nigeria.